The Influence of Changing the Educational Curriculum on Students at SD Negeri Ibu Jenab 1 Cianjur - Fitriyani Kosasih; Pipin Tadjudin; Deden Mulyadi; Usep Yunus (Edumaspul: Jurnal Pendidikan, 2022)
The aims of this study are (1) to find out differences between 2013 Curriculum and Merdeka Curriculum, (2) to compare 2013 Curriculum and Merdeka Curriculum in Elementary Schools, and (3) to analyze difficulties faced implementing 2013 Curriculum and Merdeka Curriculum in Elementary Schools, Cianjur. This type of research is qualitative research using qualitative methods, namely observation, interviews or document review. The results of study indicate that 2013 Curriculum has good concept in educational process. However, implementation in field did not run as it should. Meanwhile, implementation of Merdeka Curriculum in several Driving Schools was carried out in the first year quite well, then developed many schools in the year. Some schools are still designing right formula in implementing Merdeka Curriculum. Based this description, Merdeka Curriculum after being analyzed is better and in accordance with the Indonesian education culture than the 2013 Curriculum, programs that are forced to be implemented in education in elementary schools, especially in SD Negeri Ibu Jenab 1 Cianjur.